Simulated Antarctic sea ice expansion reconciles climate model with observation - Wei Liu (npj Climate and Atmospheric Science)
Abstract Observations reveal Antarctic sea ice expansion and Southern Ocean surface cooling trends from 1979 to 2014, whereas climate models mostly simulate the opposite. Here I use historical ensemble simulations with multiple climate models to show that sea-ice natural variability enables the models to simulate an Antarctic sea ice expansion during this period under anthropogenic forcings. Along with sea-ice expansion, Southern Ocean surface and subsurface temperatures up to 50oS, as well as lower tropospheric temperatures between 60oS and 80oS, exhibit significant cooling trends, all of which are consistent with observations. Compared to the sea-ice decline scenario, Antarctic sea ice expansion brings tropical precipitation changes closer to observations. Neither the Southern Annular Mode nor the Interdecadal Pacific Oscillation can fully explain the simulated Antarctic sea ice expansion over 1979–2014, while the sea-ice expansion is closely linked to surface meridional winds associated with a zonal wave 3 pattern.